Interstate market of charcoal in Tocantins state - Cachoeira, Jader Nunes; Silva, Allan Deyvid Pereira da; Oliveira, Lawrence Nóbrega de; Ganassoli Neto, Eduardo; Giongo, Marcos; Batista, Antonio Carlos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The production of charcoal deriving from native forests has been putting pressure on different biomes, mainly the Cerrado one, where the vegetation has been devastated to supply charcoal mining companies focused on Brazilian steel plants. Forest replenishment is an environmental management tool used to reduce pressure on natural resources, through reforestation. Data on the production of charcoal allow stipulating the amount of original forest replenishment credits to offset the use of natural resources. The objective of this work was to the current charcoal production scenario and the main consumers of charcoal deriving from native forests in Tocantins State. Forest Origin Documents regarding the period from 2009 to 2016 were provided by the Brazilian Institute of Environment and Renewable Natural Resources (IBAMA - Instituto Brasileiro do Meio Ambiente e dos Recursos Naturais Renováveis) and used as data sources. Data were inserted in a spreadsheet and subjected to descriptive statistics. Values stipulated in Resolution n°. 28, of November 22, 2011, of the State Environmental Council of Tocantins (COEMA-TO - Conselho Estadual do Meio Ambiente do Tocantins), were used to convert the amount of charcoal produced in areas of planted forests originated from forest replenishment. Tocantins State presented a scenario of constant native charcoal production increase. The annual mean production was 546,071.3 mdc (meters of charcoal) from 2009 to 2013 and it decreased to 145,128 mdc from 2014 to 2016. The main destination was Minas Gerais State, which consumed 77.01% of its production from 2009 to 2016.